The Relationship between Socio-Cultural Factors and the Practice of Exclusive Breastfeeding in Breastfeeding Mothers at the Kobe Community Health Center - Trisna Santi; Rani Safitri (Green Health International Journal of Health Sciences Nursing and Nutrition, 2026)
Exclusive breastfeeding for the first six months of life is an important effort to improve infant health and survival. Although the benefits of exclusive breastfeeding are widely known, its practice is still not optimal in various regions due to the influence of social and cultural factors. This study aims to analyze the relationship between socio-cultural factors and the practice of exclusive breastfeeding in breastfeeding mothers. The study used a descriptive analytical design with a cross-sectional approach. The sample consisted of 30 mothers with infants aged 6–12 months at the Kobe Community Health Center, selected using an accidental sampling technique. Data were collected through interviews using a structured questionnaire and analyzed univariately and bivariately using the Chi-square test and Fisher's Exact Test. The results showed that 56.7% of mothers successfully provided exclusive breastfeeding. Husband's support and family traditions had a significant relationship with the practice of exclusive breastfeeding, with p = 0.030 and p = 0.040, respectively. Mothers who received high husband's support and were in a supportive family environment had a greater chance of successfully providing exclusive breastfeeding. This study concluded that socio-cultural factors play an important role in determining the success of exclusive breastfeeding.